METTL16 accelerates lung adenocarcinoma progression by inducing N6-methyladenosine modification of GTSE1 to regulate p53 pathway and cell cycle - Fang Liu; Sheng Jin (Cell Division)
Abstract Background METTL16 has recently emerged as an N6-methyladenosine (m6A) methyltransferase that serves an integral role in tumor regulation. However, its involvement in lung adenocarcinoma (LUAD) remains unexamined. This investigation aims to explore METTL16’s role and mechanism in LUAD progression. Methods The expression of METTL16 and G2 and S phase-expressed-1 (GTSE1) in LUAD was evaluated by qRT-PCR or western blotting. LUAD cell malignancy was checked by CCK-8, wound healing, and transwell invasion assays. The relationship among METTL16 and GTSE1 was determined via Pearson correlation analysis and MeRIP assay. The p53 pathway-related proteins were detected by western blotting, and cell cycle was analyzed by flow cytometry. Results METTL16 was elevated in LUAD, and its silencing significantly reduced LUAD cell proliferation, migration, and invasion. GTSE1 was significantly downregulated upon silencing METTL16. Furthermore, increased levels of GTSE1 mRNA and protein were found in LUAD, and it was correlated positively with METTL16 in LUAD tissues. The stability of GTSE1 was modulated by METTL16 in an m6A-dependent way, and GTSE1 overexpression partially rescued the suppressive effects METTL16 silencing on LUAD cells. In addition, GTSE1 overexpression also inhibited p53 pathway to promote LUAD cell cycle. Conclusions These results indicate that METTL16-mediated m6A modification of GTSE1 accelerates LUAD progression by regulating p53 pathway and cell cycle. The aforementioned findings suggest METTL16 and GTSE1 may serve as potential targets for LUAD management.